Unfolding a Unique Tongue: A Morphological Formation of Swardspeak in a State University - Analyn Daguro Almoite (k@ta: A Biannual Publication on the Study of Languange and Literature, 2025)
Swardspeak is a unique language with distinct linguistic characteristics. This study examined the morphological formation processes of swardspeak or gay lingo, utilized in a state university. Using qualitative research, specifically discourse analysis, the morphological formation of the swardspeak used by gays at Quirino State University was investigated. The study included 80 participants who were identified as gay guys and enrolled from the three campuses, along with two gay interraters and a language teacher who assisted with data processing. The study gathered the participants' gay lingo, which served as data to examine its morphological formation processes. The findings revealed that key rules are employed in each morphological formation process, such as acronym, blending, borrowing, clipping, clipping with affixation, coinage, compounding, derivation or affixation, association, and substitution. Recognizing the specific morphological rules and incorporating various languages into their swardspeak increases the sense of belonging and shared identity among gay individuals at Quirino State University.